Stabilitasi Agegrat Tanah Dan Pengaruhnya Terhadap Penurunan Erosi Dilahan Terjal - Zalukhu, Cipria Agus Iman; Mendrofa, Elsa Greta (CV. SINAR HOWUHOWU, 2024)
Soil erosion on steep land is a major problem which results in the loss of the fertile soil layer and has an impact on reducing land productivity and environmental quality. This research aims to analyze the effectiveness of soil aggregate stabilization in reducing the rate of erosion on steep land using several methods, namely the addition of organic material, terracing and bunds. This research was carried out in situ on land with a slope of 15-30%, where each method was tested to measure its effect on reducing erosion rates. The research results showed that terracing provided the most significant reduction in erosion rates of 15.8 tonnes/ha/year, followed by bunds and the addition of organic material. Soil aggregate stabilization techniques, especially terracing, have proven effective in reducing erosion on steep land by increasing aggregate stability and slowing surface flow. These findings provide recommendations for appropriate soil stabilization methods to maintain the sustainability and productivity of steep land.